An evidence-based meta-analysis on the use of brivaracetam in treating seizures in real-world clinical practice - Zhang, Yu; Liu, Huihui; Wang, Xin; Zhao, Zhiqiang; Su, Hong; Ma, Yanjun; Zhao, Jie; Wang, Qingshan; Hou, Liyan (Frontiers in Pharmacology, 2026)
ObjectiveThe study aimed to evaluate the clinical efficacy and safety of brivaracetam (BRV) as monotherapy or adjuvant therapy for adults with seizures.MethodsObservational studies of BRV were systematically searched. We estimated the pooled incidence of interests (responder rate, seizure-free rate, adverse effects (AEs), and withdrawal rate) with their corresponding 95% confidence intervals (CIs).ResultsThirty-five studies, including 10,956 patients, were included. The 50% responder rates were 36% (95% CI: 0.26–0.47), 35% (95% CI: 0.21–0.49), and 40% (95% CI: 0.24–0.56), respectively, and the pooled seizure-free rates were 19.0% (95% CI: 0.17–0.25), 21.0% (95% CI: 0.15–0.27), and 23.3% (95% CI: 0.14–0.31), respectively, at 3, 6, and 12 months of BRV treatment. Subgroup analysis showed that although previous levetiracetam (LEV) failure can affect the response to BRV, treatment with BRV could still be beneficial for these patients. Furthermore, a remarkable reduction in seizure frequency and lower AEs were found among patients who switched directly from LEV to BRV. In addition, BRV, used as the first add-on or monotherapy, displayed a high 50% responder rate and seizure-free rate. The pooled incidence of AEs at 3, 6, and 12 months of BRV treatment were 39.0% (95% CI: 0.27–0.50), 29.0% (95% CI: 0.18–0.39), and 34.0% (95% CI: 0.25–0.44), respectively; the withdrawal rates due to AEs were 7.0% (95% CI: 0.03–0.10), 11.1% (95% CI: 0.05–0.17), and 10.0% (95% CI: 0.07–0.13) at the same follow-up point.ConclusionOur meta-analysis has shown BRV to be effective and well-tolerated in both short-term and long-term usage when used as monotherapy or adjuvant therapy for adults with seizures in real-world settings. BRV may be a valuable treatment when used as monotherapy, as a first add-on, and in patients who switched directly from LEV or previously failed to respond to or tolerate LEV.Clinical Trial Registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD420251085564.